STUDIES ON GONOCOCCUS INFECTION : IV. PILI: THEIR ROLE IN ATTACHMENT OF GONOCOCCI TO TISSUE CULTURE CELLS - Swanson, John (The Rockefeller University Press, 1973)
Attachment of Neisseria gonorrhoeae to amnion cells in tissue culture is facilitated if the gonococci bear pili. This has been determined by studying the number of pilated, colony type 2 gonococci associated with amnion cells after incubation in vitro as compared with the number of nonpilated, colony type 4 gonococci present with amnion cells under the same conditions. These data are supported by light microscope findings. Electron microscope studies provide visualization of fine structure of gonococcal attachment. Gonococci are also found within amnion cells in this in vitro system.